Situation of women and girls displaced by the violence of the boko haram terrorist group in Nigeria: Maiduguri, Borno state, North-Eastern Nigeria - Jiménez Rodríguez, María José; Erro Mugica, Saioa (Handbook of Research on Current Advances and Challenges of Borderlands, Migration, and Geopolitics, 2024)
This research aims to analyse the situation in Maiduguri, capital of Borno State, northeastern Nigeria, one of the areas hardest hit by the violence perpetrated by the terrorist group Boko Haram, which has led to the forced displacement of thousands of people who have fled their homes to safer places such as camps for internally displaced persons or refugees. Using a qualitative methodology, within the interpretative paradigm, the aim is to find out whether actions are being developed to promote gender equality and equal opportunities, to analyse the degree of involvement and awareness of the community regarding the importance of gender equality and finally, and how we could contribute from international development cooperation to improve the situation of displaced women. Thanks to the needs assessment carried out in this research, it is possible to detect existing shortcomings and draw conclusions that will serve as a basis for the design of a proposal for social intervention aimed at achieving gender equality through the promotion of women's autonomy in the Maiduguri IDP camp.
Keywords: women; girls; terrorist group; boko haram; Nigeria; Scopus(2)